Work Environment and Job Satisfaction of Soldiers with Psychological Well-being as a Moderator - Ogi Nanda Raka Ade Candra Nugraha; Adi Heryadi (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2025)
Indonesian military personnel serve as the front line in safeguarding national sovereignty and often face high job pressure and challenging work environments. These conditions can lead to stress, job dissatisfaction, and even disciplinary violations. A decrease in job satisfaction can significantly impact soldier loyalty and performance. Therefore, understanding the factors influencing job satisfaction is essential. This study aims to examine the relationship between work environment and job satisfaction and explore the moderating role of psychological well-being among soldiers of the 3rd Armed Battalion/Naga Pakca. The research utilized a quantitative correlational method, involving 177 enlisted and non-commissioned officers from the 3rd Armed Battalion/Naga Pakca. Data were gathered using three self-report scales: the work environment scale based on Soetjipto’s theory, developed into a work environment scale by Panggabean and Satwika (2024); the Job Satisfaction Scale – Luthans, adapted by Irmadani and Izzati (2024); and the Psychological Well-Being Scale – Ryff, adapted by Rijki and Kuncoro (2024). All instruments were tested for validity and reliability. Data analysis was performed using Pearson Product-Moment Correlation and Moderated Regression Analysis (MRA) with interaction testing. The findings revealed a strong and statistically significant positive relationship between work environment and job satisfaction (r = 0.707; p < 0.05). Additionally, psychological well-being was found to significantly moderate this relationship (p = 0.000), contributing 75.4% to the overall model (R²). This indicates that psychological well-being strengthens the impact of a conducive work environment on job satisfaction. In conclusion, psychological well-being plays a critical role in enhancing the positive influence of the work environment on job satisfaction among military personnel. Therefore, military institutions should prioritize supportive work environments and programs that promote mental well-being to improve soldiers' satisfaction and performance over the long term.